Women's Experiences of Using Anabolic Androgenic Steroids - Börjesson, Annica; Ekebergh, Margaretha; Dahl, Marja-Liisa; Ekström, Lena; Lehtihet, Mikael; Vicente, Veronica (Frontiers in Sports and Active Living, 2021)
Anabolic androgenic steroids are used by women to increase their muscle mass and because of their performance-enhancing effects. Despite permanent/high risk of side effects, knowledge is inadequate. Our aim has been to deepen understanding about women's use of anabolic androgenic steroids. This phenomenological study is based on the reflective lifeworld research (RLR) approach. Lifeworld interviews were conducted with 12 women, aged 21–56 years, about their experiences of using anabolic steroids. The results show that women experience a sense of pride when they successfully achieve their goals. This is the driving force, triggering tension between suffering and success. Our research adds important knowledge from a reflective lifeworld perspective and shows that women's use of anabolic androgenic steroids is a complex phenomenon. Understanding and knowledge are important in order to be able to meet and support women in their fears and difficulties.